The reception of debussism in the history of European musical modernism (on the example of the sheет music collection «Tombeau de Claude Debussy») - Deoba, S. (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2024)
The relevance of the study. One of the style pillars of modernism is the creative heritage of Claude Debussy, who held key positions on the pages of music-critical magazines, mock-ups of music publishers, and ultimately in concert programs; this trend continues to this day. Throughout the life of Debussy, his creative handwriting, moreover, his perception and imitation by other artists began to be titled debussism. Therefore, the analysis of the ways of reception of debussism is an attempt to increase the radius of Debussy’s influence on the work of modernist composers of the first third of the twentieth century. The main objectives of the study — to trigger the idea of reception in the context of the influence of Claude Debussy’s music on his contemporaries and to expand the awareness regarding the Debussy’s techniques complex that are most actively subject to reception. The research methodology: comparative (for the separation of the common and distinctive aesthetic markers between C. Debussy and the mentioned composers), structural-analytical (for the definition of the main style techniques of C. Debussy, applied by his contemporaries), complex method (for the summary for the specific receptive methods in the analyzed miniatures). Results and conclusions. After the death of the composer, the course of debussism had own characteristics notably it facilitated a more organic (and perhaps more artistically qualitative) integration of the ideas of the outstanding artist into the work of his supporters. This can be explained as the optimal time distance from the original source of the nominal phenomenon and the growing popularity of other modernist «-isms» as well. Concerning the figurative content of the analyzed compositions, actually in all cases the authors of the collection plays articulating it metaphorically «come it the territory» of Debussy, since they reproduce the ideological-figurative complexes that are typical for him. The outlined composer decisions of Paul Dukas and Florent Schmitt can be summarily considered as vivid examples of the reception of debussism. Having one figurative source (invariant) in the form of a mythological character, both composers (P. Dukas and F. Schmitt) moved along different technological routes, which once again proves their deep assimilation, re-awareness and re-formation, in a broader aspect, the interpretation of Debussy’s style markers in their own compositions. Such parallelism with Claude French serves as an indicator of the deep influence of the last one on the artistic role of his two compatriots. So the musical collection «Tombeau de Claude Debussy» (1920) presents a peculiar projection of debussism on a much wider spectrum of time - the era of modernism, and on a more local level - on the work of a number of its representatives endowed with their own original aesthetic, style and compositional features. The Debussy’s techniques adopted by different composers are added to one musical and historical picture, which is invaluable from the point of view of objectivity and is made in a multi-colored but ordered artistic and stylistic palette. Substantive acquaintance with it indicates the unique nature of musical modernism in the history of which traces of nominal and general "isms" are inextricably and sometimes inconceivably intermingled. Being the exponents of their cultural time, they encourage further study of the epochal heritage and open wide research prospects in the field of revealing the style patterns of European musical modernism.